Pengaruh Ukuran Perusahaan dan Financial Leverage Terhadap Praktik Income Smooting Pada Ukuran Indeks LQ45 Yang Terdaftar Dalam BE Tahun 2013-2017 - Mulia, Yudi Suci; Tasman, Abel (Jurnal Salingka Nagari, 2023)
The financial statements of go public companies are an important part to support movements in the capital market. The income statement is one of the important components in the financial statements. Management is required to be able to generate stable profits every year. The capital market prefers companies with stable profits to fluctuating profits. Income smoothing is one of the practices carried out by management to reduce excessive fluctuations in earnings. Income smoothing can be measured using the eckel index by comparing the variation in earnings with income. This study will examine whether firm size and financial leverage affect companies to practice income smoothing. Research data is secondary data and samples were taken using purposive sampling method. The sample consists of 21 companies that are members of the LQ45 index from 2013-2017 with a total sample of 105. This study uses a logistic regression research model because the dependent variable is a dummy variable. The results of the study reveal that 2 independent variables simultaneously have a significant effect on the practice of income smoothing. Partially, firm size and financial leverage have no significant effect on income smoothing practices.